EVALUASI KINERJA KATALIS LIMONIT SOROAKO PROSES PENCAIRAN BATUBARA BANKO SELATAN - Silalahi, Lambok Hilarius (Badan Pengkajian dan Penerapan Teknologi, 2006)
Investigation of Limonite for catalyst on South Banko coal liquefaction werecarried out under standard condition which has developed by BPPT. LimoniteSoroako is a natural mineral that found at Nickel Mining on Soroako, SouthSulawesi.Four samples of limonite was examined using 5L autoclave at our coalliquefaction laboratory in order to investigate their activities to produce highdistillate yield at standard condition (450oC, 9MPa cold H2).The results showedthat limonite S99-E-MY gave a higher distillate yield than those of other limonite(difference about 10-30%daf coal or %bkta). Further investigations wereconducted to compare with other catalysts: synthetic g?FeOOH and pyrite (FeS2).Again, the activity of limonite S99-E-MY was still superior compared to those ofsynthetic and pyrite catalysts. The yield difference was about 10-16%daf coal or%bkta).Experiment revealed that the factor of FeOOH critically affected the coalliquefaction reaction to improve the distillate yield and to reduce CLB yield.Besides, the representative of Co metal in the limonite (?5-10 %bk) could givesynergism effect with FeOOH to improve the activity of limonite.Kata Kunci: g?FeOOH, pyrite (FeS2), limonite, soroako, coal liquefaction